China's dangerous crisis - Seth, S.P. (2000)
Beijing is currently obsessed with two issues: the question of Taiwan, and the quasi-religious Falun Gong movement, which the party `apparatchiks' fear is threatening its unquestioned hold over the country. Combinedly they have the potential of plunging China into another political and social nightmare. - Reproduced
Keywords: China - Politics and government; Politics and government